2020
DOI: 10.1136/jitc-2020-001714
|View full text |Cite
|
Sign up to set email alerts
|

Immunogenic cell death pathway polymorphisms for predicting oxaliplatin efficacy in metastatic colorectal cancer

Abstract: BackgroundImmunogenic cell death (ICD) is a tumor cell death involving both innate and adaptive immune responses. Given published findings that oxaliplatin, but not irinotecan, drives ICD, we investigated whether single nucleotide polymorphisms (SNPs) in the ICD pathway are associated with the efficacy of oxaliplatin-based chemotherapy in metastatic colorectal cancer (mCRC).MethodsTwo randomized clinical trials data were analyzed: discovery cohort, FOLFOX/bevacizumab arm (MAVERICC); validation cohort, FOLFOXIR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 27 publications
1
18
0
Order By: Relevance
“…However, up to now, whether IRI can induce ICD remains controversial. A report has shown that although IRI increased the expression of DAMPs, it could not be used as an effective antitumor treatment to protect mice from tumor rechallenge [24]. Consistent with our present findings, previous studies have shown that IRI is a qualified ICD inducer [25, 26].…”
Section: Discussionsupporting
confidence: 84%
“…However, up to now, whether IRI can induce ICD remains controversial. A report has shown that although IRI increased the expression of DAMPs, it could not be used as an effective antitumor treatment to protect mice from tumor rechallenge [24]. Consistent with our present findings, previous studies have shown that IRI is a qualified ICD inducer [25, 26].…”
Section: Discussionsupporting
confidence: 84%
“…Previous studies that focused on a common missense variant GSTP1-rs1695 yielded inconsistent results (19)(20)(21). Variants in other pathways, e.g., drug transport, folate pathway, and VEGF and EGF pathways, immunogenic cell death pathway, enterocyte subtype-related genes, have also been studied without showing concrete evidence of influencing oxaliplatin efficacy (21)(22)(23)(24)(25)(26).…”
Section: Introductionmentioning
confidence: 99%
“…Insensitivity to chemotherapeutic agents and postoperative recurrence are the most difficult problems in clinical anticancer treatment, which will lead to the failure of clinical chemotherapy. Growing evidence suggests that chemotherapeutics with both cytotoxic and immunogenic properties (e.g., anthracyclines) are superior to cytotoxic drugs alone (e.g., cisplatin) against the matched patients with several similar tumor characteristics, especially for tumors with low immune infiltrates called “cold tumors” or non-T-cell-inflamed cancers, such as colorectal cancer. , …”
Section: Introductionmentioning
confidence: 99%
“…Growing evidence suggests that chemotherapeutics with both cytotoxic and immunogenic properties (e.g., anthracyclines) are superior to cytotoxic drugs alone (e.g., cisplatin) against the matched patients with several similar tumor characteristics, especially for tumors with low immune infiltrates called "cold tumors" or non-T-cell-inflamed cancers, such as colorectal cancer. 1,2 Cardiac glycosides (CGs) are an ideal class of multipotent antitumor compounds, although the initial discovery and pharmacological effects are unrelated to oncology. CGs have cytotoxic effects and, more importantly, are capable of converting nonimmunogenic events into bona fide immunogenic cell death (ICD).…”
Section: Introductionmentioning
confidence: 99%